Sistem Pengurusan Makanan Ikan - Muhammad Shazuwan Mohd Nordin; Munirah Mohd Yusof (Applied Information Technology And Computer Science, 2021)
Aquaculture technology is becoming increasingly essential as a means of boosting protein supplies. As a result, workers physically feed fish, for example, by going to a farm or pond and throwing fish food into the pond. The fish feed management system is a software and hardware system designed to assist fish farmers in monitoring feeding fish, water quality, and temperature in livestock ponds. The system development life cycle is supported by prototype approach. Laravel software was utilized to create the system, while PHP was employed as the programming language. The system employs Arduino technology to control the equipment that feeds the fish and measures the pH and temperature of the water in the tank. Users will be able to utilize this system to feed physical food and monitor the quality of pond water while guaranteeing that the fish are in good health, saving time in the process.